A semi-crystalline carbonaceous structure as a wide-spectrum-responsive photocatalyst for efficient redox catalysis. Issue 41 (26th April 2021) - Yang, Pengju; Wang, Ruonan; Zhang, Hongxia; Zhao, Jianghong; Wang, Peng; Shi, Hu; Yang, Hengquan
Abstract : A wide-spectrum-responsive carbonaceous photocatalyst was developed for the first time. This carbonaceous structure can efficiently catalyze hydrogen synthesis and benzyl alcohol oxidation under visible light, even under NIR light irradiation. Abstract : Herein, we synthesized an oxygen- and nitrogen-containing carbonaceous structure (ONCS). This ONCS possessed exceptional light-harvesting ranging from the visible to NIR light region. Characterization results confirmed that the ONCS was an n-type semiconductor. The ONCS can efficiently catalyze hydrogen photosynthesis and benzyl alcohol oxidation under visible light, even under NIR light irradiation.